1969
DOI: 10.1111/j.1432-1033.1969.tb00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Glucagon and Insulin on the Metabolism of Perfused Livers from Fasted Rats

Abstract: Glucagon (28 nM) stimulated gluconeogenesis, urea production and ketogenesis in perfused livers from fasted rats. Since the livers were perfused without added substrate, liver protein is the source of carbon of the glucose synthesis. Addition of N6, O2′‐dibutyryl cyclic adenosine 3′:5′‐monophosphate in concentrations of 100 and 10 μM to the perfusion medium resulted in a response similar to that of glucagon. It is suggested that cyclic adenosine 3′:5′‐monophosphate is the mediator of glucagon action in liver. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…5 Cherrington, A. D., et al Manuscript in preparation. regulating glucose production-by the liver after an ovemight fast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Cherrington, A. D., et al Manuscript in preparation. regulating glucose production-by the liver after an ovemight fast.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, in the anesthetized dog fasted over-INTRODUCTION The ability of glucagon to increase hepatic glucose production has been well documented both in vivo (1)(2)(3) and in vitro (4,5). Similarly, the inhibitory action of insulin on glucose output has been clearly established (6)(7)(8)(9)(10).…”
mentioning
confidence: 95%
“…It is possible that other abnormalities might also influence the development of hepatic autophagy. A reduced concentration of insulin in the presence of a high glucagon level augments hepatic gluconeogenesis in the perfused rat liver preparation (24)(25)(26)(27)(28). This effect has been demonstrated even when amino acids are omitted from the perfusate (24), suggesting that hepatic amino acids are among the precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the ability of glucagon to stimulate these two processes in man has been questioned (8,9). The assessment of the lipolytic and ketogenic activity of glucagon in man has been complicated by the inherent capability of glucagon to stimulate insulin secretion (14) and the fact that insulin inhibits both lipolysis and ketogenesis (2,(15)(16)(17). Indeed, early studies in vivo in various species, including man, showed a marked decline in circulating free fatty acids (FFA) after glucagon administration (18)(19)(20)(21)(22), attributed to the observed rise in plasma immunoreactive insulin (IRI)1 (23,24).…”
Section: Introductionmentioning
confidence: 99%